Sharp Bounds for Generalized m-Linear n-Dimensional p-Adic Hardy-Littlewood-Pólya Operator. (4th October 2021) - Li, Xiang; Zhang, Xiran; He, Qianjun
Abstract : In this paper, we study the sharp bounds for the generalized m -linear n -dimensional p -adic Hardy-Littlewood-Pólya operator on central and noncentral p -adic Morrey spaces with power weight. As an application, the sharp bounds for the p -adic Hardy-Littlewood-Pólya operator on corresponding Morrey spaces are obtained. These results generalize substantially some well-known results.